Disorder-induced cubic phase in Fe2-based Heusler alloys - Kiss, Janos; Chadov, Stanislav; Fecher, Gerhard H.; Felser, Claudia (Physical Review B - Condensed Matter and Materials Physics, 2013)
Based on the first-principles electronic structure calculations, we analyze the chemical and magnetic mechanisms stabilizing the cubic phase in Fe 2-based Heusler materials, which were predicted to be tetragonal when being chemically ordered. In agreement with recent experimental data, we found that these compounds crystallize within the so-called "inverted" cubic Heusler structure perturbed by a certain portion of the intrinsic chemical disorder. Understanding of these mechanisms is a necessary step to guide the successful future synthesis of the stable Fe2-based tetragonal phases, which are promising candidates for the rare-earth-free permanent magnets. © 2013 American Physical Society.
CRIS-Team Scopus Importer:2023-03-20